Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan pada Sicepat Ekspres Kota Bima - Muhammad Nur; Intisari Haryanti; Ovriyadin Ovriyadin (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
In the current modern era, the development of the services industry in the logistics sector is increasingly increasing, development of online business and also the increasing number of applications that provide opportunities for people to carry out buying and selling transactions online, so that expedition companies in Indonesia certainly take advantage of the opportunities that exist. The purpose of this research is to determine the influenceof quality, sevice and price on customer satisfaction. The obiect of this research is the customers of Sicepat ekspres Bima city branch. This research uses quantitative methods with anassociative type. The data collection technique in this research uses questionnaires with Accidental Sampling techniques. Observation, Questionnaire, Literature Study, Validity Test, Rehabilitation Test. Classical assumption test, multiplinear regression,multilinear coefficients, determination test, T test and Ftest. The results of this research show that X1 service quality and X2 price have a positive and significant influence simultaneously on Y customer satisfaction. X2 price has a positive but not partially significant influence on Y customer satisfaction, however X2 service quality is positive and significant influence on Y customer satisfaction. Bima City Branch Sicepat Expedition.